(untitled) (Journal of the College of Languages (JCL), 2025)
Translation is the element which characterizes colleges and departments of languages and translation. These academic institutions are concerned in qualifying high quality staffs which carry out translation as profession at the state and society institutions. Experts in translation believe that translation is an applied science depends heavily on the skills of the translator which he/ she acquire in the course of exercising it. Otherwise, translation remains restricted within the field of theories. Press is a suitable application field for translation where translators find in press an area of mass spread enables them to show their talents and to widen their spread circle. Hence, "Azzaman" paper, Iraq version, initiative started; dedicating a weekly page titled "Translations" to publish the translations done by the members of the teaching staffs of colleges and departments of translation at the Iraqi universities. Any academic institution has a specified identity springs from its aims, mission and vision. Translation, in this respect, is the distinctive identity of colleges and departments of languages and translation. In the light of this fact, translation is described as science and art at the same time. It requires skills and capabilities a translator cannot acquire them without exercising translation continuously to monitor his/ her performance level and responses to his/ her production. Thus, application field is a crucial criterion to evaluate translator capacity to apply the materials he/ she learnt. The present paper attempts to analyze the content of "Translations" page of "Azzaman" daily, subjugate it to the scientific methodology in order to specify the nature of the subjects published there, the languages translated from ’Source’ and the basic data concerning the translators